Persepsi Kepuasan Komunikasi Organisasi Karyawan Pt. Eds Manufacturing Indonesia (PEMI) - Bela, Andini Ratna; Mukarromah, Al (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
The purpose of this study to determine how the perception of organizational communication satisfaction of employees at PT. PEMI, PT. EDS Manufacturing Indonesia manufacturing automotive wiring harness. The company was founded in 1989 and based in Tangerang Indonesia PT. PEMI operates as a subsidiary of Yazaki which is owned by a Japanese company, PT. PEMI is a pioneer of industry wiring harness, manufacture of car body cable. Wairing harness is a collection of one or more wires with several parts conducting electric current. This company managed to give satisfaction to almost all employees who work in this company. The focus of the problem in this study to determine how the perception of organizational communication satisfaction in the company pemi. The research method used is descriptive qualitative research method. While primary data sources are employees at PT. PEMI, while secondary data sources of documents, books related to the author. This theory suggests that communication satisfaction is defined as individual satisfaction with various aspects of communication that exist in the organizational environment, this theory identifies eight communication satisfaction in the organization, namely Climate Communication, Supervisory Communications, Organizational Integration, Media Quality, Horizontal Informal Communication, General Organizational Perspective, Subordinate, Feedback. Data collection techniques are by conducting interviews, observation and documentation, to obtain descriptive data, in the form of written or spoken words from people and observable behavior, and drawing conclusions. The results of this study show that there are 8 points that the authors found about the perception of organizational communication satisfaction of employees of PT. PEMI, namely, First the communication climate in the pemi company is all good, second the communication of superiors with subordinates is very alert if there are problems related to work, Third The Information System Management work environment in this company is good, fourth the quality of communication management here the information provided is always delivered on time and directed, fifth the informal communication and horizontal communication used is informal, sixth the employee's understanding of the company's condition employees really understand the development of the company's ups and downs, seventh communication subordinates to superiors, employees are very well respond to what is ordered by his superiors, eighth feedback in the company provides a reward in the form of cash and promotion.